2014
DOI: 10.1016/j.micres.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of aflatoxin B1 by an aqueous extract from leaves of Adhatoda vasica Nees

Abstract: The effectiveness of aqueous extracts of various medicinal plants in detoxification of aflatoxin B1 (AFB1) was tested in vitro by thin-layer chromatography and enzyme-linked immunosorbent assay (ELISA). Among the different plant extracts, the leaf extract of Vasaka (Adhatoda vasica Nees) showed the maximum degradation of AFB1 (≥ 98%) after incubation for 24h at 37 °C. The aflatoxin detoxifying activity of the A. vasica leaf extract was significantly reduced by heating to 100 °C for 10 min or autoclaving at 121… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 34 publications
3
54
0
3
Order By: Relevance
“…Researcher claimed that the herbal drug AV may be used in the treatment of Alzheimer. [76] Along with above-said beneficial health effects, the AV also showed few other activities which have indirect effect on human health conservation, namely, antifungal, [77,78] larvicidal, [79][80][81] anticestodal, [82] and acaricidal. [83] Although AV has been used as a medicine from long back and claimed to be safe for the use as medicine [78] still few adverse effects have also been reported like cytotoxicity, [84] adverse reaction in the form of urticaria, exanthema, and contact dermatitis in Sweden population.…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…Researcher claimed that the herbal drug AV may be used in the treatment of Alzheimer. [76] Along with above-said beneficial health effects, the AV also showed few other activities which have indirect effect on human health conservation, namely, antifungal, [77,78] larvicidal, [79][80][81] anticestodal, [82] and acaricidal. [83] Although AV has been used as a medicine from long back and claimed to be safe for the use as medicine [78] still few adverse effects have also been reported like cytotoxicity, [84] adverse reaction in the form of urticaria, exanthema, and contact dermatitis in Sweden population.…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…Hence there is an urgent need to develop or investigate the biological methods which prevent the production of aflatoxin or prevents activity. It is well established that several authors reported that some medicinal plants have the potential to destroy aflatoxin [9,25]. There were several reports of higher levels of aflatoxins in the cultivated groundnut based cattle and poultry feeds.…”
Section: Molecular Identification Of Isolated Strainmentioning
confidence: 99%
“…Several detoxification studies with microorganisms and physical agents for aflatoxin detoxification showed structural alterations in aflatoxin molecules after detoxification [9,29]. Ciegler et al (1966) tested a large number of microbial populations for their ability to detoxify the fungal toxin, AFB1 and observed formation of a new fluorescing compound with concomitant disappearance of AFB1, when toxin was added to acid-producing mold cultures [30].…”
Section: Molecular Identification Of Isolated Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…Five major compounds, including 3-(hydromethyl)-8, 9-dihydro-2H-furo[2, 3-h]chromen-8-ol, 1-hydroxy-2-oxo-5-(2, 4, 6-trihydroxy-2, 3, 3a, 8a-tetrahydrofuro[2, 3-b]benzofuran-5-yl)cyclopentanecarboxylic acid, 2-(2, 4-dihydroxy-2, 3, 3a, 8a-tetrahydrofuro[2, 3-b]benzofuran-5-yl)-5-hydroxycyclopent-1-enecarboxylic acid, 1-hydroxy-2-(4-hydroxy-6-methoxy-2-oxo-2, 3, 3a, 8a-tetrahydrofuro[2, 3-b]benzofuran-5-yl)-5-oxocyclopentanecarboxylic acid, and 1, 2-dihydroxy-5-(4-hydroxy-2-oxo-2, 3, 3a, 8a-tetrahydrofuro[2, 3-b]benzofuran-5-yl)cyclopentanecarboxylic acid, were revolved and identified from the degradation product by using UPLC-Q-TOP-MS, and the addition reaction was mainly responsible for AFB 1 decomposition. All the five degradation products lost their double bonds in the terminal furan ring and hence theoretically had reduced toxicity compared with AFB 1 according to the structure-activity by many microorganisms, enzymes [9], and the extract of some plants [11], and hence, the biological decontamination of AFB 1 appears attractive, but this method may have certain disadvantages in that the organisms would utilize food nutrients for their growth and release undesirable metabolites [12].…”
Section: Can Be Degradedmentioning
confidence: 99%